Pharmacological properties of endemic plants growing in the steppes of Kazakhstan (Eurasian Journal of Ecology, 2019)
The number of people who suffer from secondary immunodeficiency diseases is increasing. Secondary immunodeficiency diseases develop due to environmental degradation, abuse of various preservatives, stabilizers in foods and long-term storage products, abuse of the use of drugs with a cytostaticeffect, the use of antibiotics in the cultivation of cattle and poultry. The compoundswere obtained fromplants of the Halostachys caspica (Pall) C.A.Mey.ex Schrenk,Suaeda microphylla Pall., Climacoptera obtusifolia (Schrenk) Botsch.Plant extracts were investigatedon myelostimulating activity. The compoundobtained from plants of the Halostachys caspica (Pall) C.A.Mey.ex Schrenk by means of water-alcoholextractionwithout heating showed high myelostimulating activity. It effectively stimulated erythro-,thrombocyto- and leukopoiesis, and in stimulating the leukocyte population, it equally effectively increased the values of granulocyte and agranulocyte leukocytes. The compounds derived from the Suaedamicrophylla Pall. and Climacoptera obtusifolia (Schrenk) Botsch.showed low myelostimulating activity.It should be noted that the water-alcohol extracts of plants without heating showed higher activity thanthe extracts that have undergone thermal heating.Key words: myelostimulating activity, endemic plants, steppes of Kazakhstan.